Hepcidin downregulation by repeated bleeding is not mediated by soluble hemojuvelin - Krijt, J; Fujikura, Y; Sefc, L; Vokurka, M; Hlobenová, T; Necas, E (Physiological research, 2010)
Hepcidin is a key regulator of iron homeostasis, while hemojuvelin is an important component of the hepcidin regulation pathway. It has been recently proposed that soluble hemojuvelin, produced from hemojuvelin by the protease furin, decreases hepcidin expression. The aim of the presented study was to examine the downregulation of hepcidin by chronic bleeding in hemojuvelin-mutant mice. Male mice with targeted disruption of the hemojuvelin gene (Hjv-/- mice) and wild-type littermates were maintained on an iron-deficient diet and subjected to weekly phlebotomies for 7 weeks. Gene expression was examined by real-time PCR. In wild type mice, repeated bleeding decreased hepcidin mRNA by two orders of magnitude. In Hjv-/- mice, basal hepcidin expression was low; however, repeated bleeding also decreased hepcidin mRNA content by an order of magnitude. Phlebotomies reduced hepatic iron overload in Hjv-/- mice by 80 %. Liver and muscle furin mRNA content was not significantly changed. No effect on hepatic Tmprss6 mRNA content was observed. Results from the study indicate that soluble hemojuvelin is not the sole factor responsible for hepcidin downregulation. In addition, the presented data suggest that, under in vivo conditions, tissue hypoxia does not transcriptionally regulate the activity of furin or TMPRSS6 proteases.
Keywords: kationické antimikrobiální peptidy; játra; Hemochromatosis Protein; Membrane Proteins; Iron Overload; Hemorrhage; erytropoéza; messenger RNA; Serine Endopeptidases; Down-Regulation; hypoxie buňky; flebotomie; hepcidiny; Time Factors; zvířata; myši; GPI-Linked Proteins; down regulace; dietní železo; Hepcidins; časové faktory; Antimicrobial Cationic Peptides; Mice; myši knockoutované; Erythropoiesis; kosterní svaly; RNA, Messenger; Liver; Phlebotomy; serinové endopeptidasy; Male; Mice, Knockout; Iron, Dietary; Furin; Muscle, Skeletal; protein hemochromatózy; furin; membránové proteiny; krvácení; Animals; přetížení železem; GPI-vázané proteiny; deficit železa; mužské pohlaví; Disease Models, Animal; Cell Hypoxia; Iron Deficiencies; modely nemocí na zvířatech